The Impacts of Industrial Revolution 4.0 on the Rights of Persons with Disabilities - Trang, Nguyen Thu (VNU Journal of Science: Legal Studies, 2019)
We are at the dawn of the industrial revolution 4.0. What will the industry 4.0 impact on the rights of people with disabilities. This paper aims at exploring the primary issues in connection with the impacts of the industry 4.0 on the rights of people with disabilities. This paper is therefore divided into four sections. The first section will provide an overview of the industry 4.0, the second section will provide an overview of the rights of people with disabilities, the third section will analyze the impacts of industry 4.0 on the rights of people with disabilities, and the last one will produce some recommendations for ensuring the rights of people with disabilities in the industry 4.0.